Analisis Pengaruh Variabel EPS dan Makroekonomi terhadap Return Saham Jakarta Islamic Index Sektor Pertanian - Nurrahmah Apriyani; Wiwiek Rindayati; Ranti Wiliasih (AL-MUZARA'AH, 2015)
The agricultural sector of islamic stock has a downward trend of return and often gives negative return, thereby it reduces the interest of investors to buy similar stocks. This study aims to examine the effect of Earning Per Share (EPS), exchange rate, money supply, SBI interest rate and world gold prices toward stock return of PT Astra Agro Lestari Tbk (AALI) and stock return of PT PP London Sumatra Indonesia Tbk (LSIP) as representatives of agricultural stock. The method used is the Vector Error Correction Model (VECM) with monthly time series data from August 2011 to December 2014. In the long term, the results showed that the EPS significantly positive  effect on the return of AALI and LSIP , exchange rates significantly positive effect on the return of LSIP, money supply significantly negative effect on the return of AALI and LSIP, SBI interest rate significantly negative effect on the return of LSIP and world gold prices significantly negative effect on the return of AALI. Money supply predominantly contribute toward the changes of the return of AALI and LSIP.